KEBUTUHAN INVESTOR TERHADAP INFORMASI KINERJA PEMERINTAH DAERAH KABUPATEN BANYUMAS DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Oman Rusmana; Alfian Pradana Baskoro Putra; Sukirman Sukirman (Jurnal Manajemen Indonesia, 2015)
This study is a research used mixed methods that focused to combine two approaches, quantitative and qualitative on user of Local Government Finance Report (LKPD) in Banyumas Regency. The purpose of this study were determine the needs of investors, investor information that used in LKPD, relationship between respondents and their description of reading LKPD, suitability of infrastructure information in LKPD to user needs, and the factors that affect the infrastructure reporting in LKPD. Based of research and data analysis using Chi Square test (Fisher's Exact), descriptive statistics methods and qualitative analysis show that: (1) The need for investors to invest in Banyumas is a good investment climate, (2) The information used by investors in the LKPD Banyumas in making investment decisions are government policy, evaluation of services, information infrastructure, and information regarding the BPK audit opinion LKPD, (3) There is a relationship between readers / non-readers LKPD and the category of respondents, (4) There is a relationship between respondents by reason of reading LKPD, (5) There is the relationship between the importance of infrastructure information and respondents of readers LKPD, (6) There was no relationship between the time required to read LKPD and the importance of information infrastructure, (7) Disclosure aspects of financial infrastructure in the LKPD Banyumas Regency is not appropriate with the needs of users, (8) Disclosure aspects of non-financial infrastructure in Banyumas LKPD is not fully appropriate with the needs of users (9) Factors that affecting disclosure of infrastructure in LKPD of Banyumas Regency are: council recommendation, Government Accounting Standards, recommendation of Badan Pemeriksa Keuangan and local government policy